Peranan Aktivitas Hadrah Dalam Pembentukan Akhlak Mudia di Cembing Trimulyo Jetis Bantul - Santi Kustiwi (FAI UMY, 2017)
Peranan Aktivitas Hadrah Dalam Pembentukan Akhlak Mudia di Cembing Trimulyo Jetis Bantul